A framework for implementing mobile enterprise resource planning (m-ERP) system to improve healthcare services in Zimbabwe. - Jaravaza, Kefasi (Midlands State University, 2020)
This study sought to develop a framework for the implementation of mobile Enterprise Resource Planning (m-ERP) System to improve healthcare services in Zimbabwe: A case of Chitungwiza central hospital. Information was gathered using a case study research strategy accompanied with interviews, questionnaire, records review and observation approaches. In recent years, due to the development of cloud computing and portable devices, a new mobility era is starting. The popularity of smartphones and tablet computers has changed the behavior of mobile-phone users and enhanced the development of more integrated functions for ERP systems users to operate and access company information through various mobile devices anywhere, anytime. However, mobile ERP is still in the development stage. On the whole, there has been relatively little research into the framework and system implementation of healthcare mobile ERP systems until recently. Participants were selected from patients and staff members at Chitungwiza central hospital. The results obtained suggested that there is need to develop a framework for the implementation of mobile ERP system to improve healthcare services in Zimbabwe. The evidence collected reflects that top management involvement is key to the successful implementation of the mobile ERP system. There is need for gaining trust and support from top management as they are the ones who avail resources for successful implementation of the mobile ERP system. The proposed framework suggested a three-tier mobile ERP system involving database, connect and user interface. There are also issues that must be addressed before moving the data to a mobile computing environment, namely: individual, corporate, strategic well as security issues. These issues have to be address at every stage for successful implementation of the mobile ERP system. The study recommended that for Chitungwiza central hospital to gain competitive advantage, it is important to allocate sufficient time towards proper training of users, involving users from the project commencement, gain support and trust from the top management. In addition, enough resources must be allocated towards the problem while involving qualified and experienced people to be part of the project team to avoid loss of company resources. Mobile ERP system is supported by mobile computing, which is the ability to access resources from anywhere at any time. Future research can explore on the storage capacity and mobile data encryption in aggregation with the proposed mobile ERP implementation framework